Reduction in ambulatory distance from childhood through adolescence: The impact of the number and length of steps - Roseane de Fátima Guimarães, PhD; Kapria-Jad Josaphat, PhD; Ryan Reid, PhD; Mélanie Henderson, MD, PhD; Tracie Ann Barnett, PhD; Marie-Eve Mathieu, PhD (Elsevier, 2021)
Background: The aim of this study was to explore the relationship between ambulatory distance with steps/day and increased step length as children age. Methods: This is a prospective cohort study. Forty-five children from the QUALITY cohort were assessed at childhood (baseline) and seven years later during adolescence (follow-up). Daily step count was evaluated by accelerometry, step length by a standardized test, and daily ambulatory distance was calculated based on step count and length. Results: Children grew by an average of 0.33 m from childhood to adolescence (p < 0.001). The daily ambulatory distance decreased by an average 3008 m from childhood to adolescence (p < 0.001). Step length increased an average of 0.10 m (p < 0.001) from childhood to adolescence, while the number of steps taken decreased by an average of 5549 steps (childhood to adolescence) (p < 0.001). The change in the number of steps between childhood and adolescence represents 84.6% of the change in the ambulatory distance while the change in step length explained an additional 13.0% Conclusions: The decrease in the ambulatory distance from childhood to adolescence was strongly explained by the decrease in step count; however the increase in step length should not to be neglected.